Evaluasi Program Pelayanan Sosial terhadap Anak Terlantar di Lembaga Kesejahteraan Sosial Yayasan Sayap Ibu - Muhammad Andra Nurramadhan; Irhamni Rahman (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
This research was conducted to analyze the process of providing social services for abandoned children at the Sayap Ibu Foundation. Abandoned children are seen as a group with a high level of vulnerability and therefore require special intervention in fulfilling basic rights, protection, and developing their personal capacity so they can develop optimally. The research method applies a qualitative approach that uses interview processes, observations, and documentation studies to obtain the required information. Research findings show that the services provided include aspects of protection, education, fulfillment of basic needs, and psychosocial development which are implemented in an integrated manner by professional staff and volunteers. In its implementation, this service still faces a number of obstacles, including limited human resources, infrastructure, and minimal support from the community, which has an impact on the suboptimal service. However, the Sayap Ibu Foundation still has a significant contribution in improving the welfare of abandoned children through various programs oriented towards social rehabilitation, character strengthening, and empowerment. Therefore, it can be concluded from this study that it is necessary to strengthen comprehensive and sustainable services, as well as closer collaboration between institutions, government and the community in order to increase the effectiveness of handling neglected children by utilizing the functions and roles of foundations to the maximum. Then, the implications of the results of this study can be used as consideration for policy makers and social actors in designing more effective service programs for neglected children.